g) 1990x92-89x 1990+3x1990x9=
Răspunsuri la întrebare
Răspuns de
1
Explicație pas cu pas:
1990 × ( 92 - 89 + 3× 9) = 1990 × ( 3+27) = 1990 × 30 =
Răspuns de
0
1990x92-89x1990+3x1990x9
=183 080-177 110+5970x9
=183 080-177 110+53 730
=5970+53 730
=59 700
=183 080-177 110+5970x9
=183 080-177 110+53 730
=5970+53 730
=59 700
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Informatică,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă